Access Site Complications and Management of the Transradial Approach for Neurointerventions. Issue 2 (11th August 2022) - Weinberg, Joshua H.; Sweid, Ahmad; Asada, Ashlee; Schaefer, Joseph; Ruiz, Ramon; Kang, KiChang; Gooch, Michael Reid; Herial, Nabeel A.; Tjoumakaris, Stavropoula; Zarzour, Hekmat; Rosenwasser, Robert H.; Jabbour, Pascal
Abstract : BACKGROUND: The transradial approach has increasingly been used for neurointerventions because of the improved safety profile compared with transfemoral. However, it is important to be aware of potential complications such as radial artery (RA) spasm, RA occlusion, pseudoaneurysm, extravasation, arteriovenous fistula, and wrist hematoma as well as their management. OBJECTIVE: To present our institution's experience with the prevention and management of local access site complications associated with the transradial approach for neuroendovascular interventions. METHODS: We conducted a retrospective analysis of a prospectively maintained database and identified 1524 consecutive neuroendovascular procedures performed using transradial access from April 2018 to February 2021. RESULTS: Among 1524 procedures, local transradial complications occurred in 1.7%. Major complications occurred at a rate of 1.2% including RA extravasation (0.3%), delayed RA occlusion (0.6%), pseudoaneurysm (0.1%), compartment syndrome (0.1%), infection (0.1%), and avulsion of the RA in 0.1% (1 of 1524) with no serious clinical consequence. Although RA occlusion is included in major complications, all cases were asymptomatic and did not require any intervention. Minor complications occurred at a rate of 0.5% including severe RA spasm (0.3%) and hematoma (0.3%). No patient in the cohort died or suffered from permanent disability from a complication related to the transradial approach. CONCLUSION: Transradial access for neurointervention has a low rate of local complications, particularly when taking appropriate prevention measures. Appropriate management of complications can prevent procedural failure and has low morbidity rates demonstrating the overall safety profile of transradial access even when complications occur.